Emotions and Their Influence on Our Personal, Interpersonal and Social Experiences 2018
DOI: 10.4324/9781315100319-8
|View full text |Cite
|
Sign up to set email alerts
|

Faces of Shame: Implications for Self-Esteem, Emotion Regulation, Aggression, and Well-Being

Abstract: General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.-Users may download and print one copy of any publication from the public portal for the purpose of private study or research-You may not further distribute the material or use it for any profit-making activity or commercia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 13 publications
2
18
0
Order By: Relevance
“…However, theoretical contributions (Rogier & Velotti, 2018a) and preliminary empirical data suggest that emotion regulation abilities may play an important role in such relationship. Besides, difficulties in emotional regulation would be the basis of maladaptive functioning modalities (Garofalo & Velotti, 2015;Velotti, Garofalo, Bottazzi & Caretti, 2017a;Velotti Garofalo, Callea, Bucks, Roberton & Daffern, 2017b) and hence are regarded as a fertile soil for both GD and PD (Rogier & Velotti, 2018b).…”
Section: Introductionmentioning
confidence: 99%
“…However, theoretical contributions (Rogier & Velotti, 2018a) and preliminary empirical data suggest that emotion regulation abilities may play an important role in such relationship. Besides, difficulties in emotional regulation would be the basis of maladaptive functioning modalities (Garofalo & Velotti, 2015;Velotti, Garofalo, Bottazzi & Caretti, 2017a;Velotti Garofalo, Callea, Bucks, Roberton & Daffern, 2017b) and hence are regarded as a fertile soil for both GD and PD (Rogier & Velotti, 2018b).…”
Section: Introductionmentioning
confidence: 99%
“…Studying PTSD, social anxiety and internalized shame is of great importance due to following reasons. First, welfare and eminence of life are momentously contributed by the nonappearance of psychological difficulties (Hoge et al, 2006;Velotti, Garofalo, Bottazzi, & Caretti, 2017;Zafar et al, 2016). Second, for post-trauma retrieval, greater stages of communal care / satisfaction, self-appraisal, and better coping strategies offer resilience and flexibility, and lack of these qualities lead toward the prevalence of psychological problems (Nawaz, Khalily, & Gul, 2018;Waqas et al, 2018).…”
Section: Mediating Role Of Shame Between Ptsd Symptoms and Social Anxmentioning
confidence: 99%
“…The anti-social behaviors of individuals with highly anti-social behaviors are more serious, stable, and aggressive in their childhood and adolescence. Both domestic and foreign research has found that the school bullying is related to the personalities of students [3][4][5][6]; it has indicated that the emotions of school bullying victims are unstable and impulsive, which are especially sensitive to external stimuli such as the pressure stimuli that cannot be relieved timely. school bullying greatly affects the personality characteristics of adolescent students.…”
mentioning
confidence: 99%